Study on the Stability of the Coal Seam Floor above a Confined Aquifer Using the Structural System Reliability Method - Haifeng Lu; Xiuyu Liang; Nan Shan; You-Kuan Zhang (Geofluids)
A quantitative method of structural system reliability was proposed to study the influence of random rock mechanical parameters and loads on the stability of the coal seam floor above confined aquifers. To obtain the reliability probability of the floor, two modes of water-resistant floor failure were suggested as follows: (1) mining completely removed the water-resistant key strata of the floor. In this case, the failure modes were of three main types: mining failure, confined water intrusion, and combined mining failure and intrusion. (2) Failure modes included shear and tensile failures when the thickness of the key strata was greater than 0. On the basis of the elastic thin plate theory, the performance function that calculates the reliability probability of all modes could be obtained. The failure modes were regarded as the series system. The Monte Carlo method was employed to calculate the reliability probability of each failure mode and series system. The results showed that the random rock mechanical parameters and loads of the key strata significantly influence the antiwater inrush capacity of the floor. In addition, the water inrush coefficient and reliability probability can be simultaneously used as the evaluation indexes of water inrush risk. Both these indexes could improve the assessment of the reliability of the floor.